Kinetic Parameters of the Conversion of Methane Precursors to Methane in a Hypereutrophic Lake Sediment - Strayer, Richard F. (1978)
The kinetic parameters K(m), V(max), T(t) (turnover time), and v (natural velocity) were determined for H(2) and acetate conversion to methane by Wintergreen Lake sediment, using short-term (a few hours) methods and incubation temperatures of 10 to 14°C. Estimates of the Michaelis-Menten constant, K(m), for both the consumption of hydrogen and the conversion of hydrogen to methane by sediment microflora averaged about 0.024 μmol g(−1) of dry sediment. The maximal velocity, V(max), averaged 4.8 μmol of H(2) g(−1) h(−1) for hydrogen consumption and 0.64 μmol of CH(4) g(−1) h(−1) for the conversion of hydrogen to methane during the winter. Estimated natural rates of hydrogen consumption and hydrogen conversion to methane could be calculated from the Michaelis-Menten equation and estimates of K(m), V(max), and the in situ dissolved-hydrogen concentration. These results indicate that methane may not be the only fate of hydrogen in the sediment. Among several potential hydrogen donors tested, only formate stimulated the rate of sediment methanogenesis. Formate conversion to methane was so rapid that an accurate estimate of kinetic parameters was not possible. Kinetic experiments using [2-(14)C]acetate and sediments collected in the summer indicated that acetate was being converted to methane at or near the maximal rate. A minimum natural rate of acetate conversion to methane was estimated to be about 110 nmol of CH(4) g(−1) h(−1), which was 66% of the V(max) (163 nmol of CH(4) g(−1) h(−1)). A 15-min preincubation of sediment with 5.0 × 10(−3) atm of hydrogen had a pronounced effect on the kinetic parameters for the conversion of acetate to methane. The acetate pool size, expressed as the term K(m) + S(n) (S(n) is in situ substrate concentration), decreased by 37% and T(t) decreased by 43%. The V(max) remained relatively constant. A preincubation with hydrogen also caused a 37% decrease in the amount of labeled carbon dioxide produced from the metabolism of [U-(14)C]valine by sediment heterotrophs.